Spectroscopic confirmation of the low-latitude object FSR 1716 as an old globular cluster - Koch-Hansen, Andreas; Kunder, Andrea; Wojno, Jennifer (Astronomy and astrophysics, 2017)
Star clusters are invaluable tracers of the Galactic components and the discovery and characterization of low-mass stellar systems can be used to appraise their prevailing disruption mechanisms and time scales. However, owing to significant foreground contamination, high extinction, and still uncharted interfaces of the underlying Milky Way components, objects at low Galactic latitudes are notoriously difficult to characterize. Here, we present the first spectroscopic campaign to identify the chemodynamical properties of the low-latitude star cluster FSR 1716. While its photometric age and distance are far from settled, the presence of RR Lyrae variables indicates a rather old cluster variety. Using medium-resolution (R ~ 10 600) calcium triplet (CaT) spectroscopy obtained with the wide-field, multi-fiber AAOmega instrument, we identified six member candidates with a mean velocity of −30 km s-1 and a velocity dispersion of 2.5 ± 0.9 km s-1. The latter value implies a dynamic mass of ~ 1.3 × 104M⊙, typical of a low-mass globular cluster. Combined with our derived CaT metallicity of −1.38 ± 0.20 dex, this object is finally confirmed as an old, metal-poor globular cluster.